Special educational institutions as subjects of prevention of deviant behavior of minors in Russia at the end of the 20th century - S. A. Brazhnikov (Омский научный вестник: Серия "Общество. История. Современность")
Within the framework of the scientific article, the historical experience of the organization of the functioning of the Russian system of special educational institutions for minors with deviant behavior in the 90s of the twentieth century is studied. The author objectively shows the picture of the evolution of special education and upbringing in the context of the transition of the state to market relations. Conclusions based on the results of the study characterize at the national level the place and role of special educational institutions in the system of subjects of prevention of behavioral deviations of minors, as well as the state of work on the development of a network of such institutions in the Russian Federation.